Determinants Of Labor Absorption in Eastern Indonesia - Wafiqah Ulya; Rahmatia Rahmatia; Sabir Sabir; Hamrullah Hamrullah (Institute of Computer Science (IOCS), 2022)
This study aims to determine and analyze the effect of government spending, minimum wage and investment on employment through economic growth in Eastern Indonesia. This study uses secondary data obtained from the Central Statistics Agency (BPS), the Investment Coordinating Board (BKPM) and the Directorate General of Fiscal Balance (DJPK). The data used is panel data consisting of 13 Provinces in Eastern Indonesia (KTI) in 2012-2021. The data analysis method used is the Structural Equation Model (SEM). Based on the results of this study indicate that government spending has a negative and insignificant effect on employment through economic growth. While the minimum wage has a negative and significant effect on employment through economic growth and investment has a positive and significant effect on employment through economic growth in Eastern Indonesia (KTI).